2009
DOI: 10.1371/journal.pone.0007405
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Fingerprints Identify miR-150 as a Plasma Prognostic Marker in Patients with Sepsis

Abstract: BackgroundThe physiopathology of sepsis continues to be poorly understood, and despite recent advances in its management, sepsis is still a life-threatening condition with a poor outcome. If new diagnostic markers related to sepsis pathogenesis will be identified, new specific therapies might be developed and mortality reduced. Small regulatory non-coding RNAs, microRNAs (miRNAs), were recently linked to various diseases; the aim of our prospective study was to identify miRNAs that can differentiate patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
272
4
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(296 citation statements)
references
References 35 publications
15
272
4
5
Order By: Relevance
“…In mice and rats, miR-150-5p, upregulated in samples captured by membrane affinity, was increased by polymicrobial sepsis and LPS treatment, respectively [60,61]. Vasilescu et al reported plasma levels of miR-150-5p to correlate with sepsis aggressiveness in a cohort of 17 sepsis patients [62]. In concordance with previous findings in critically ill patients, we detected miR-122-5p as upregulated in samples derived from all isolation methods.…”
Section: Discussionmentioning
confidence: 99%
“…In mice and rats, miR-150-5p, upregulated in samples captured by membrane affinity, was increased by polymicrobial sepsis and LPS treatment, respectively [60,61]. Vasilescu et al reported plasma levels of miR-150-5p to correlate with sepsis aggressiveness in a cohort of 17 sepsis patients [62]. In concordance with previous findings in critically ill patients, we detected miR-122-5p as upregulated in samples derived from all isolation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate miRNAs from the profiles were miR-150, miR-182, miR-342-5p, miR-486 and miR-132, miR-146a, miR-155 and miR-223. Plasma levels of miR-150 decreased significantly 53 while serum miR-146a and miR-223 were significantly reduced in septic patients compared with controls. 54 Not only are new biomarkers for determining the severity of the condition important, new biomarkers are also needed in the search for septic treatment.…”
Section: Circulating Mirnas In Tissue Injury and Infectionmentioning
confidence: 87%
“…Detection methods need adjustment to minimize protocol-based bias, and the strategy of raw data normalization is a critical issue. So far, several normalization strategies for the analysis of circulating miRNAs are available, such as using literature-based tissue housekeeping genes or miRNAs as normalizers, 28,32,37,53,56 which has been challenged by the fact of unstable expression of these "tissue normalizers" in serum. 15,19,57 Normalizing serum miRNA expression by using equal amounts of serum across all samples has also been adopted, which may be insufficient as our lab and others have noticed the considerable variations in RNA quantities extracted from equal volumes of serum from different individuals.…”
Section: Circulating Mirnas In Tissue Injury and Infectionmentioning
confidence: 99%
“…Our group observed in plasma of septic patients, that miR-150 is significantly downregulated and that its value correlates with the aggressiveness of the disease. We proposed miR-150 as a new biomarker for sepsis (51). In a recent study, Tudor et al found 12 deregulated miRNAs in plasma of septic patients.…”
Section: The Mechanisms Behind the Complications The Mechanisms Behinmentioning
confidence: 98%